Faktor manajerial yang mempengaruhi layanan luar gedung puskesmas di desa dan kota: analisis IFLS East (Berita Kedokteran Masyarakat (BKM), 2018)
Purpose: This study aims to find the managerial factors affecting outside services of public health center in urban and rural.Method: IFLS East 2012 data analysis.Results: Heads of non-physician public health center in the rural often provide outside services rather than the heads of physician's public health center in the urban. Posyandu and counseling 15 times more often performed by heads of non-doctoral public health center in the rural.Conclusion: Heads of physician's public health center often conduct administrative activities and seminars. While the heads of non-physician health center often conduct field visits. Public health center in the rural have more outside services of than in the urban.